2015
DOI: 10.1080/09168451.2015.1018125
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nrf2/Keap1 signaling and autophagy induction against oxidative stress in heart in iron deficiency

Abstract: We investigated the effects of dietary iron deficiency on the redox system in the heart. Dietary iron deficiency increased heart weight and accumulation of carbonylated proteins. However, expression levels of heme oxygenase-1 and LC3-II, an antioxidant enzyme and an autophagic marker, respectively, in iron-deficient mice were upregulated compared to the control group, resulting in a surrogate phenomenon against oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Iron is an essential element for cellular responses, including immune response and oxidative metabolism (7,25). Previously, we reported that iron deficiency induced oxidative stress in the liver and heart (10,34). However, limited information is available on the molecular mechanisms underlying the association between oxidative stress and autophagy during iron deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Iron is an essential element for cellular responses, including immune response and oxidative metabolism (7,25). Previously, we reported that iron deficiency induced oxidative stress in the liver and heart (10,34). However, limited information is available on the molecular mechanisms underlying the association between oxidative stress and autophagy during iron deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Iron deficiency increases oxidative stress in NIH3T3 cells (10). First, we examined to clarify accumulated intracellular ROS levels using the same cell line.…”
Section: Iron Deficiency Increased Cellular Ros Productionmentioning
confidence: 99%
See 3 more Smart Citations